Characterization of a class II ketol-acid reductoisomerase from Mycobacterium tuberculosis. Issue 17 (6th April 2022) - Valera, Ane; Wang, Shan; Carr, Reuben; Trembleau, Laurent; Deng, Hai
Abstract : Biochemical characterization of an unusual class II KARI (MtKARI-II) from a Mycobacterium tuberculosis variant. Abstract : Mycobacterium tuberculosis ketol-acid reductoisomerases have been widely studied due to their metabolic importance towards development of drug-resistant bacteria treatment. We here report the biochemical characterization of a new KARI (MtKARI-II) from a Mycobacterium tuberculosis variant with a similar kinetic profile to class I KARIs. Phylogenetic analysis suggested that MtKARI-II is clustered into a class II KARI superfamily.